Problem of Desertification in Arid Zone of Rajasthan - A View - Dhir, R P (Annals of Arid Zone, 2016)
Though vicissicitudes have occurred in the past. the climate with its assemblage of good and bad years is believed to have remianed steady from the historic period upto the present. The dominant sandy soils have high basic erodibility but arc conservative of moisture and fertile enough 10 support a vegetation cover as is permitted by the rainfall regime. The natural vegetation is diverse. well adapted. largely palatable and efficient builder of biomass. Therefore while granting an ecological fragility to the area. the natural endowments arc not the root cause for all the degradation taking place in the arid region of western Rajasthan. The tract has a long history of human settlement and land use but the past six-seven decades. have witnessed a vast expansion of crop-based landuse. This has occurred partly at the cost of the earlier fallow farming system but mainly by taking cultivation onto new lands including the dunes and the areas where climate is only marginally conducive to farming. The change is the direct outcome of the rising human population and man's increased competence. The situation has lead to a greatly increased incidence of wind erosion and generation of drift sands, including appearance of branches.However. overall the land productivity losses arc fortunately mild so far though other costs arc considerable. A more serious consequence of man's intervention has been in the open pasturelands. where more than two thirds of the area is in a state of largely severe degradation. Declining water table in good aquifers due to over exploitation is another alarming development. Scientific research has given a set of technologies and likewise impressive strides have been made in development of irrigation. electrification. means of communication, drinking water supply and afforestation. However. application of technologies has been tardy and environmental content of development effort is meagre. The crying need is containment of biotic pressure. reverting of marginally suited lands to pastures and a scientifically sound management of resources.